El suicidio y sus aplicaciones al caso Mac Swiney alcalde de Cork (Terence MacSwiney) - De Artibay, A. (Bilbao : Tipografía del Nervión, 1926)
Catholic study on the religious implications of the death of Terence MacSwiney, Lord Mayor of Cork as a result of the hunger strike which he embarked upon after being sentenced to two years imprisonment in a court martial, as a protest against the British government and the British presence in Ireland.